Artistry on ice : figure skating skills and style - Kerrigan, Nancy, 1969- (Human Kinetics, 2003)
"Artistry on Ice gives you an in-depth look at advanced techniques for jumps, spins, and freestyle moves in addition to body alignment and refining footwork, music, and expression. It shows you what it takes to excel from the perspective of one of figure skating's champions." "Four chapters are devoted solely to competition, covering the music, choreography, costumes, and other elements to create the ultimate performance. Also included are renowned trainer Igor Burdenko's insights on physical preparation for powerful and fluid skating." "From triumphs over personal tragedy to her superb performance under pressure in the 2000 Goodwill Games, Kerrigan prevailed against many challenges during her 20-year career. Now she teams with former competitive figure skater and professional instructor Mary Spencer to share the insight that will take your skating to the top."--BOOK JACKET.